FIGHTING ILLIBERALISM: THE ROLE OF AWARENESS RAISING PROJECTS (Annals of the University of Bucharest. Political Science Series, 2024)
Illiberalism recently became a favourite catchphrase of several political actors around the world. Although not necessarily precise, the term conjures alternative understandings of democracy, by contesting the inherent need of a democratic political system to be intimately tied to liberal values. This lack of precision is often instrumentalized to boost popular support for taking measures leading to discrimination and resisting or even fighting pluralism. This text aims to familiarize the reader with the existing conceptual debates surrounding the concept of illiberalism, while also offering a glimpse into the causes responsible for its popularity. Theoretical knowledge is then juxtaposed with information regarding an awareness raising project aiming to fight illiberalism in countries of Central and Eastern Europe. The conclusion stresses the need for communication and education campaigns regarding the perils of illiberalism, especially in the more fragile democratic contexts of post-communist Europe. Citizens need to be aware of how illiberalism endangers democracy, as well as have at their disposal mechanisms for raising awareness regarding illiberal measures taken by various governments.
Keywords: illiberalism; Central and Eastern Europe; post-communism; democracy; awareness-raising project; civil society